Role of Sodium-Glucose Cotransporter Inhibitors in the Management of Heart Failure: A Position Statement - Mohanan, PP; Chopra, Vijay Kumar; Yadav, Rakesh; Dalal, Jamshed; Das, Mrinal Kanti; Ray, Saumitra; P, Harikrishnan; Kerkar, Prafulla (Cardiology and Cardiovascular Medicine, 2023)
Heart Failure (HF) is a chronic debilitating condition, which affects millions globally. India has recorded the second-highest increase in the number of HF cases worldwide, along with the second-highest 1-year mortality outcome for HF. Despite significant progress in the management of HF, the mortality and morbidity rates remain unacceptably high, which indicates unmet needs in HF management. Accumulating evidence has established consistent cardiovascular and renoprotective effects of sodium–glucose cotransporter 2 inhibitors (SGLT2i), irrespective of diabetes status. The overall safety and benefits of SGLT2i in the context of HF hospitalization and mortality have been acknowledged by recent guidelines. The benefits of SGLT2i have been established for HF persons with reduced ejection fraction (HFrEF). Consequently, SGLT2i including dapagliflozin and empagliflozin has been positioned among the first-line therapy in the treatment algorithm for HFrEF by the European Society of Cardiology 2021 guidelines. Recent findings indicate similar benefits of SGLT2i in HF persons with preserved ejection fraction (HFpEF). Moreover, SGLT2i fulfills the criteria for a potential therapeutic option for cardiorenal syndrome. Therefore, SGLT2i is a strong candidate to be positioned as a potent disease-modifying therapy for HF with wide acceptance by clinicians.